Impact of Tumour Epstein-Barr Virus Status on Clinical Outcome in Patients with Classical Hodgkin Lymphoma (cHL): A Review of the Literature and Analysis of a Clinical Trial Cohort of Children with cHL - Nohtani, Mahdi; Vrzalikova, Katerina; Ibrahim, Maha; Powell, Judith E; Fennell, Éanna; Morgan, Susan; Grundy, Richard; McCarthy, Keith; Dewberry, Sarah; Bouchal, Jan; Bouchalova, Katerina; Kearns, Pamela; et al. (Cancers, 2022)
In this study, we have re-evaluated how EBV status influences clinical outcome. To accomplish this, we performed a literature review of all studies that have reported the effect of EBV status on patient outcome and also explored the effect of EBV positivity on outcome in a clinical trial of children with cHL from the UK. Our literature review revealed that almost all studies of older adults/elderly patients have reported an adverse effect of an EBV-positive status on outcome. In younger adults with cHL, EBV-positive status was either associated with a moderate beneficial effect or no effect, and the results in children and adolescents were conflicting. Our own analysis of a series of 166 children with cHL revealed no difference in overall survival between EBV-positive and EBV-negative groups (p = 0.942, log rank test). However, EBV-positive subjects had significantly longer event-free survival (p = 0.0026). Positive latent membrane protein 1 (LMP1) status was associated with a significantly lower risk of treatment failure in a Cox regression model (HR = 0.21, p = 0.005). In models that controlled for age, gender, and stage, EBV status had a similar effect size and statistical significance. This study highlights the age-related impact of EBV status on outcome in cHL patients and suggests different pathogenic effects of EBV at different stages of life.